TLR2/TLR5 Signaling and Gut Microbiota Mediate Soybean-Meal-Induced Enteritis and Declined Growth and Antioxidant Capabilities in Large Yellow Croaker (Larimichthys crocea) - Lei Zheng; Chao Zeng; Wanqin Zhu; Jiaonan Zhang; Lei Wang; Jianchun Shao; Wei Zhao (Journal of Marine Science and Engineering)
Soybean meal, renowned for its high yield, cost efficiency, and protein richness, serves as a pivotal plant-based alternative to fish meal. However, high soybean meal inclusion in Larimichthys crocea diets is linked to enteritis and oxidative damage, with unknown mechanisms. Our study aims to elucidate the molecular basis of soybean-meal-induced enteritis and its impact on intestinal microbiota in L. crocea. To this end, four isonitrogenous and isolipidic diets with varying soybean meal levels (0% FM, 15% SBM15, 30% SBM30, and 45% SBM45) were administered to L. crocea for 8 weeks. The results indicated that the SBM30 and SBM45 treatments significantly hindered fish growth, digestive efficiency, and protein utilization. Furthermore, high soybean meal levels (SBM30 and SBM45) activated intestinal Toll-like receptors (TLR2A, TLR2B, TLR5, and TLR22), stimulating C-Rel and mTOR protein expression and elevating ERK phosphorylation. This led to increased pro-inflammatory cytokine production (IL-1β, IL-6, and TNF-α) and decreased anti-inflammatory cytokine expression (IL-4/13A, IL-4/13B, and TGF-β), suggesting a potential signaling pathway for soybean-meal-induced enteritis. Furthermore, enteritis induced by high soybean meal levels led to oxidative damage, evident from increased MDA levels and decreased antioxidant enzyme activities (SOD and CAT). The SBM30 and SBM45 treatments increased Firmicutes and Bacteroidetes abundance in fish gut microbiota, while Proteobacteria abundance decreased. This microbiota shift may enhance soybean meal nutrient utilization, yet high soybean meal concentrations still impair growth. A soybean-meal-rich diet promotes harmful bacteria like Rhodococcus and depletes probiotics like Ralstonia, increasing disease risks. L. crocea has limited tolerance for soybean meal, necessitating advanced processing to mitigate anti-nutritional factors. Ultimately, exploring alternative protein sources beyond soybean meal for fish meal replacement is optimal for L. crocea.